Construction of unital matrix polynomials with mutually distinct characteristic roots - Mel'nyk, O. M. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
We investigate the construction of unital matrix polynomials with mutually distinct characteristic roots, namely, their similarity and reducibility by the similarity transformation to block-triangular, block-diagonal, and, in particular, to triangular and diagonal forms. We also study the problem of extracting linear factors.